Violence in Hyperreality: The Ideological Development of the Black Mirror Series (2011–2023) - Stoch, Magdalena (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2025)
Black Mirror (2011–2023) is a British television drama that combines thriller and science fiction conventions. So far, six seasons have been released, sparking many discussions about how to portray the dystopian future of Western societies. However, the last season brought a sudden turn towards the nostalgic past and horror using folklore motifs. The author uses concepts from the theories of Jean Baudrillard (“simulacra,” “hyperreality”), Guy Debord (“society of the spectacle”), Erving Goffman (“theatrical metaphor”), Michel Foucault (“panopticon,” “biopolitics”) and Shoshana Zuboff (“surveillance capitalism”) to answer the question: what is the ideological evolution of the series and has it retained its critical potential?